Contato, elos de ligação e vínculo na relação psicanalítica - Harary, Ângela Maria Moraes (2007)
The purpose of this paper is to discuss what happens during a psychoanalytic experience, when something with a potential for change and growth is generated and what kind of linking favors it. Also, it runs through a fundamental psychic phenomenon of a specific symbiotic quality, capable of a high degree of regenerative and/or constitutive parts of the self. This paper is justified by the fact that more and more the psychoanalytic process has been seen as a result of the pair s interpenetration (transference/ countertransference) and for what is stimulated in the analyst as knowledge about his/her patient psychodynamics. Some clinical hypotheses have been put forward to explain the occurrences of phenomena that are analogous to a kind of immersion in affectionate dimensions of low awareness but necessary to achieve a deep affectionate interaction that would keep symbiotic fusion fantasies. Seven topics are highlighted in order to corroborate to the institution of a link that could support this symbiotic process and the intensity of the emotions present on it: comprehension, love, confidence, loss, truth, companionship and closeness X distance. Results of this research related to clinical aspects are the maternal holding function, as an integrating experience that follows and supports moments of turbulence, a kind of safety net under the trapeze offering security and also the phenomenon of a symbiosis as a fundamental constitutive part of the psychism. This development of the libido previous to the PS ↔ D oscillation could be part of the same dynamics and then, would be turned into a three-part circulation process: symbiotic, disintegrated, integrated